The ANALISIS PENGARUH PENDIDIKAN, KESEHATAN, DAN UPAH TERHADAP PRODUKTIVITAS TENAGA KERJA DI PROVINSI NUSA TENGGARA BARAT TAHUN 2018-2021 - Thesa Nur Alviona (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2023)
Labor productivity describes the ability of workers to produce output. If the output produced by a worker is high, it indicates the higher the level of worker productivity. The quality of labor will affect the productivity of the resulting output. Labor productivity in the Province of West Nusa Tenggara is lower when compared to other provinces in Indonesia. This study aims to analyze the effect of education, health and wage variables on labor productivity in West Nusat Tenggara in 2018-2021. The data in this study are secondary data obtained from the Central Statistics Agency (BPS) of West Nusa Tenggara in 2022. The analytical method used in this study is panel data regression with quantitative descriptive analysis method. Analytical This research method is Fixed Effect Model (FEM). The results of this study indicate that the health variable has a negative and significant effect on labor productivity. Wages have a positive and significant effect on labor productivity.